Incidence, prevalence, and burden of health problems in elite female ice hockey players - A one-season prospective study - Wörner, T.; Eek, F. (Translational Sports Medicine, 2025)
Introduction: Epidemiological studies on elite female ice hockey players are lacking but needed to tailor preventive efforts in this growing group of athletes. Therefore, the aim of this study was to describe the incidence, prevalence, and burden of health problems in elite female ice hockey players.